Creating the Perfect Storm: A New Perspective of Service Quality - Rifdah Isyraq Rahmita; Teofilus Teofilus (Journal of Social Research, 2025)
This study aims to examine the influence of service quality and store atmosphere on store patronage with customer satisfaction as a mediating variable, as well as to test the moderating role of store atmosphere. The research object is Toko Salmah, a semi-modern retail store in Balikpapan. A quantitative approach was employed using a Likert-scale questionnaire distributed to 150 respondents selected through purposive sampling. Data were analyzed using Moderated Mediation Regression Analysis (MMRA) with PROCESS Macro Model 59 in SPSS. The results indicate that service quality has a positive and significant effect on customer satisfaction (b = 0.603; p < 0.001), and customer satisfaction has a positive and significant effect on store patronage (b = 0.556; p < 0.001). Furthermore, customer satisfaction mediates the effect of service quality on store patronage. However, store atmosphere was not found to be a significant moderator but acts as a direct predictor of customer satisfaction (b = 0.345; p = 0.006) and store patronage (b = 0.207; p = 0.021). These findings highlight that service quality and customer satisfaction are the primary drivers of customer loyalty, while store atmosphere contributes as a direct predictor rather than as a moderating factor. The study provides practical implications for local retailers in designing service strategies and shopping experiences that prioritize customer satisfaction.